Improving sales and marketing collaboration : a step-by-step guide - Malshe, Avinash. (2014 digital library., 2015)
In any company, sales and marketing are the two primary business functions that are focused on creating satisfied customers. Because of their complementary orientations and objectives, these two functions are ideally positioned for a fruitful, synergetic collaboration. Unfortunately, the practical reality in many companies is far removed from this utopia. Sales and marketing personnel fail to communicate effectively, resulting in misunderstandings, lack of communication, frustration, and sometimes even downright anger and sabotage. Instead of supporting each other in creating superior value for customers, sales and marketing fight tiresome internal battles that are a drain on profits, efficiency and customer satisfaction.